PERSONALLY ORIENTED LEARNING TECHNOLOGIES FOREIGN LANGUAGE IN HIGHER EDUCATION - L.V. Melnyk (Academy of Cognitive and Natural Sciences, 2007)
The purpose of this article is basis expedience of application of integrative approach to technologies of studies in trade education. It is shown that through a didactics constituent it is possible to carry out integration of technologies of study.